Amnestic mild cognitive impairment and incident dementia and Alzheimer's disease in geriatric depression. (December 2014) - Steffens, David C; R McQuoid, Douglas; Potter, Guy G; Koopmans, Raymond; Rosness, Tor
ABSTRACT Background: Memory impairment in geriatric depression is understudied, but may identify individuals at risk for development of dementia and Alzheimer's disease (AD). Using a neuropsychologically based definition of amnestic mild cognitive impairment (aMCI) in patients with geriatric depression, we hypothesized that patients with aMCI, compared with those without it, would have increased incidence of both dementia and AD. Methods: Participants were aged 60 years and older and consisted of depressed participants and non-depressed volunteer controls. The depressed cohort met criteria for unipolar major depression. All participants were free of dementia and other neurological illness at baseline. At study entry, participants were administered a standardized clinical interview, a battery of neurocognitive tests, and provided a blood sample for determination of apolipoprotein E genotype. A cognitive diagnosis was assigned by a panel of experts who convened annually and reviewed available clinical, neuropsychological and laboratory data to achieve a consensus cognitive diagnosis to determine a consensus diagnosis. Survival analysis examined the association between aMCI and later dementia (all-cause) and AD. Results: Among 295 depressed individuals, 63 (21.36%) met criteria for aMCI. Among 161 non-depressed controls, four (2.48%) met aMCI criteria. Participants were followed for 6.28 years on average. Forty-three individuals developed dementia, including 40 (13.6%) depressed and three (1.9%) control participants. Both aMCI and age were associated with incident dementia and AD. Conclusions: The presence of aMCI is a poor prognostic sign among patients with geriatric depression. Clinicians should carefully screen elderly depressed adults for memory impairment.